2016
DOI: 10.14348/molcells.2016.0167
|View full text |Cite
|
Sign up to set email alerts
|

Cell-SELEX Based Identification of an RNA Aptamer for Escherichia coli and Its Use in Various Detection Formats

Abstract: Escherichia coli are important indicator organisms, used routinely for the monitoring of water and food safety. For quick, sensitive and real-time detection of E. coli we developed a 2′F modified RNA aptamer Ec3, by Cell-SELEX. The 31 nucleotide truncated Ec3 demonstrated improved binding and low nano-molar affinity to E. coli. The aptamer developed by us out-performs the commercial antibody and aptamer used for E. coli detection. Ec3(31) aptamer based E. coli detection was done using three different detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Except S1, the biotin tag appears to hinder the binding of aptamers to the target sites. This is very important as most aptamers are selected through the SELEX or cell-SELEX process without the biotin tag, while they are often used in biosensors with a biotin tag [ 28 , 33 ]. The understanding of this discrepancy of binding is critical for the design of biosensors.…”
Section: Resultsmentioning
confidence: 99%
“…Except S1, the biotin tag appears to hinder the binding of aptamers to the target sites. This is very important as most aptamers are selected through the SELEX or cell-SELEX process without the biotin tag, while they are often used in biosensors with a biotin tag [ 28 , 33 ]. The understanding of this discrepancy of binding is critical for the design of biosensors.…”
Section: Resultsmentioning
confidence: 99%
“…68 Dua et al generated a 2'F modified RNA aptamer Ec3 by whole-cell SELEX to target E. coli DH5 α. 69 They developed an aptamer Ec3-based gap capacitance biosensor for electrochemical impedance spectroscopy (EIS); it has the detection limit of 2 × 10 4 CFU/mL for E. coli cells without any labeling and signal amplification techniques. 69 Renders et al conducted whole-cell SELEX to select ssDNA aptamers with a tyrosinelike side chain against live E. coli DH5 α cells.…”
Section: E Colimentioning
confidence: 99%
“…69 They developed an aptamer Ec3-based gap capacitance biosensor for electrochemical impedance spectroscopy (EIS); it has the detection limit of 2 × 10 4 CFU/mL for E. coli cells without any labeling and signal amplification techniques. 69 Renders et al conducted whole-cell SELEX to select ssDNA aptamers with a tyrosinelike side chain against live E. coli DH5 α cells. 70 They reported that aptamer 8.28A possesses high selectivity and affinity for the target cells and was greatly enriched for phenolmodified dU nucleotides.…”
Section: E Colimentioning
confidence: 99%
“…Aptamer sequences are usually identi ed through the SELEX (systematic evolution of ligands by exponential enrichment) process, which starts with incubating the ssDNA or RNA library with the target, followed by separation and exponential ampli cation of the binding ssDNA or RNA (Torres-Chavolla and Alocilja, 2009). By repeating this process 8-20 times before cloning and sequencing the oligonucleotides that bind to the target, the most suitable aptamers can be identi ed (Dua et al, 2016). Aptamers can be selected for a wide variety of targets, from small molecules to whole cells (Bruno, 2015;Cao et al, 2009;Sypabekova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%